Photoprotective effects of glucomannan isolated from Candida utilis - Ruszová, Ema; Pávek, Stanislav; Hájková, Veronika; Jandová, Šárka; Velebný, Vladimír; Papežíková, Ivana; Kubala, Lukáš (Carbohydrate research, 2008)
Glucomannans belong to yeast and fungal cell wall polysaccharides with known immunostimulatory and radioprotective effects. However, glucomannan protective effects against pathological consequences of skin exposure to short wavelength solar light, ultraviolet (UV) radiation, are unclear. Herein, a highly branched glucomannan (GM) isolated from the cell wall of Candida utilis, a member of the alpha-(1-->6)-D-mannan group, was tested for its photoprotective effects in an in vitro model of UVB-irradiated human keratinocytes and an in vivo model of UV-induced erythema formation in human volunteers. GM suppressed the UVB-induced decrease of keratinocyte viability, which was connected with the suppression of UVB-induced keratinocyte apoptosis. GM reduced UVB-mediated caspase activation together with suppression of DNA fragment release into the cytoplasm. Furthermore, GM suppressed UVB-induced gene expression of pro-inflammatory markers including nuclear factor kappa B, inducible nitric oxide synthase, interleukins 8 and 1, together with suppression of prostaglandin E2 and interleukin 1alpha protein release. In vivo, GM decreased UV-induced skin erythema formation, which was correlated with a decrease of phosholipase A(2) activity within the stratum corneum. It could be concluded that GM isolated from C. utilis possesses significant photoprotective effects on human keratinocytes in vitro as well as in vivo.
Keywords: Erythema; hodnocení léčiv; financování organizované; keratinocyty; apoptóza; ultrafialové záření; zánět; biologické markery; Keratinocytes; Biomarkers; Apoptosis; mannany; erytém; lidé; Ultraviolet Rays; kultivované buňky; Inflammation; Financing, Organized; Cells, Cultured; Drug Evaluation; Radiation-Protective Agents; exprese genu; Candida; Cell Survival; viabilita buněk; Mannans; Gene Expression; radioprotektivní látky; Humans